Pleonastična nikalnica v slovenskem jeziku in vprašanje dvoumnosti - Ambrožič, Urša (Jezik in slovstvo, 2020)
Cursory proofreading of a text does not enable differentiation between sentential negation and pleonastic negation in Slovenian. Only in-depth analysis can lead us to a better understanding of the role of pleonastic negation in certain syntactic environments. The norm based on this role defines the environments in which the use of pleonastic negation is obligatory, but in some cases, depending on the use, it also allows variability. Understanding a language is partially connected to a person's subjective perception; therefore, this kind of variability can stimulate thoughts about a difference in meaning between the two propositions, which can ultimately mean two completely contradictory interpretations due to the meaning seemingly overlapping. The present paper recapitulates certain restrictions of meaning that must be taken into consideration when deciding whether or not to use pleonastic negation, as its use (usually based on instinct) is not consistent and introduces disarray in meaning into the text through the formation of analogical structures. In this regard, the paper advises caution when dealing with decisive texts of legal importance, as any kind of ambiguity in meaning could have significant consequences in people's lives.
Keywords: ambiguity; dvoumnost; pleonastic negation; pleonastično zanikanje; pragmatičnost; pragmatism; skladnja; Slovenian language; slovenščina; syntax; variability; variantnost